Anti-Tumor and Anti-Invasive Effects of ONC201 on Ovarian Cancer Cells and a Transgenic Mouse Model of Serous Ovarian Cancer - Fan, Yali; Wang, Jiandong; Fang, Ziwei; Pierce, Stuart R.; West, Lindsay; Staley, Allison; Tucker, Katherine; Yin, Yajie; Sun, Wenchuan; Kong, Weimin; Prabhu, Varun; Allen, Joshua E.; et al. (Frontiers in Oncology, 2022)
ONC201 is a promising first-in-class small molecule that has been reported to have anti-neoplastic activity in various types of cancer through activation of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) as well as activation of mitochondrial caseinolytic protease P (ClpP). The present study was to explore the anti-tumor potential effect of ONC201 in ovarian cancer cell lines and in a transgenic mouse model of high grade serous ovarian cancer under obese (high fat diet) and lean (low fat diet) conditions. ONC201 significantly suppressed cell proliferation, induced arrest in G1 phase, and increased cellular stress and apoptosis, accompanied by dual inhibition of the AKT/mTOR/S6 and MAPK pathways in OC cells. ONC201 also resulted in inhibition of adhesion and invasion via epithelial–mesenchymal transition and reduction of VEGF expression. Pre-treatment with the anti-oxidant, N-acetylcysteine (NAC), reversed the ONC201-induced oxidative stress response, and prevented ONC201-reduced VEGF and cell invasion by regulating epithelial–mesenchymal transition protein expression. Knockdown of ClpP in ovarian cancer cells reduced ONC201 mediated the anti-tumor activity and cellular stress. Diet-induced obesity accelerated ovarian tumor growth in the KpB mouse model. ONC201 significantly suppressed tumor growth, and decreased serum VEGF production in obese and lean mice, leading to a decrease in tumoral expression of Ki-67, VEGF and phosphorylation of p42/44 and S6 and an increase in ClpP and DRD5, as assessed by immunohistochemistry.. These results suggest that ONC201 may be a promising therapeutic agent to be explored in future clinical trials in high grade serous ovarian cancer.